Women's equal representation in the higher judiciary: a case for judicial diversity in India. Issue 2 (3rd April 2023) - Mittal, Gita; Jain, Dipika
ABSTRACT: Diversity is an inherent feature of democratic nations. However, in many democracies such as India, the judiciary does not reflect the rich diversity of the country. Most judges in the Supreme Court and High Courts in India are cis-gender, upper-caste men. This homogenises the perspective on law and justice. Women judges and lawyers are faced with structural barriers such as gender stereotypes, discrimination, harassment, and insufficient institutional and infrastructural support. Additionally, caste, class, sexuality, and religious identity are some factors that create multiple axes of oppression to contend with. Through a critical examination of various feminist lenses, we highlight the systemic and implicit biases that lead to disproportionately low numbers of women judges. We then recommend institutional reforms that could facilitate the creation of a more diverse higher judiciary in India.